Usability of the Video Head Impulse Test: Lessons From the Population-Based Prospective KORA Study - Heuberger, Maria; Grill, Eva; Saǧlam, Murat; Ramaioli, Cecilia; Müller, Martin; Strobl, Ralf; Holle, Rolf; Peters, Annette; Schneider, Erich; Lehnen, Nadine (Frontiers in Neurology, 2018)
Objective: The video head impulse test (vHIT) has become a common examination in the work-up for dizziness and vertigo. However, recent studies suggest a number of pitfalls, which seem to reduce vHIT usability. Within the framework of a population-based prospective study with naïve examiners, we investigated the relevance of previously described technical mistakes in vHIT testing, and the effect of experience and training. Methods: Data originates from the KORA (Cooperative Health Research in the Region of Augsburg) FF4 study, the second follow-up of the KORA S4 population-based health survey. 681 participants were selected in a case-control design. Three examiners without any prior experience were trained in video head impulse testing. VHIT quality was assessed weekly by an experienced neuro-otologist. Restrictive mistakes (insufficient technical quality restricting interpretation) were noted. Based on these results, examiners received further individual training. Results: Twenty-two of the 681 vHITs (3.2%) were not interpretable due to restrictive mistakes. Restrictive mistakes could be grouped into four categories: slippage, i.e. goggle movement relative to the head (63.6%), calibration problems (18.2%), noise (13.6%), and low velocity of the head impulse (4.6%). The overall rate of restrictive mistakes decreased significantly during the study (12% / examiner within the first 25 tested participants and 2.1% during the rest of the examinations, p<0.0001). Conclusion: Few categories suffice to explain restrictive mistakes in vHIT testing. With slippage being most important, trainers should emphasize the importance of tight goggles. Experience and training seem to be effective in improving vHIT quality, leading to high usability.